Levantamento da mastofauna terrestre de médio e grande porte em remanescente de floresta neotropical – Itatinga, SP - Carvalho, Fernando Careli de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Brazil´s Atlantic coastal forest biome is considered one of the richest and most exuberant biodiversity of the whole planet. Still, other data shows the reality of this Brazilian forest: more than 93% of its original formation has been already devastated, being the human actions the greatest threat to the perpetuation of the balance and diversity of this ecosystem. This destruction affects all the fauna and flora, with even greater impact on medium and large mammals, due to its high demand on the availability of resources, living area and sensitivity to disturbances. However, today it is known the vital importance of these mammals in the preservation and maintenance of biological systems. Thus, the purpose of this study was to survey the species richness of medium and large mammals in a remnant neotropical forest located in Itatinga, SP,Brazil, using the indirect method of recording (traces on sand-plots, marking territorial, faeces, carcasses, scratches on tree trunks and vocalizations) and camera trapping. Data were collected during ten (10) consecutive months in the year 2008, from February to November. Within twenty-five plots of sand installed and monitored during the ten months were found fifteen (15) species of terrestrial mammals of medium and large, five (5) orders and twelve (12) families. Among them, we highlight the presence of threated species like the puma (Puma concolor), the deer (Mazama gouazoubira) and the giant anteaters (Myrmecophaga tridactyla). The chosen method showed up effective in raising terrestrial mammalian species of medium and large neotropical forest area, having a good applicability and advantages over other existing methods. The study area presents a huge diversity of species and, therefore, this work it is recommended to be only the beginning of new researches in the area in order to enrich... (Complete abstract click electronic access below)

O bioma da Mata Atlântica é considerado um dos mais ricos e exuberantes em biodiversidade de todo planeta. Ainda assim, outro dado mostra a realidade desta floresta brasileira: mais de 93% de sua formação original já foi devastada, sendo as ações antrópicas a maior ameaça ao equilíbrio e perpetuação da diversidade deste ecossistema. Tal destruição afeta toda a fauna e flora, tendo impacto ainda maior sobre a mastofauna de médio e grande porte, devido ao seu elevado grau de exigência quanto à disponibilidade de recursos, área de vida e sensibilidade à perturbações. Contudo, hoje se conhece a vital importância destes mamíferos na preservação e manutenção dos sistemas biológicos. Desta maneira, o objetivo do presente trabalho foi realizar um levantamento da riqueza de espécies de mamíferos de médio e grande porte em um remanescente de floresta neotropical do bioma Mata Atlântica localizado em Itatinga, SP, utilizando o método de registro indiretos (rastros em parcelas de areias, marcações territorialistas, fezes, carcaças, arranhões em troncos de árvores e vocalizações) e armadilhamento fotográfico. Os dados foram coletados durante dez (10) meses consecutivos no ano de 2008, de fevereiro a novembro. Nas vinte e cinco parcelas de areia instaladas e monitoradas durante os dez meses foram encontradas quinze (15) espécies de mamíferos terrestres de médio e grande porte, de cinco (5) ordens e doze (12) famílias. Dentre elas, destaca-se a presença de espécies ameaçadas de extinção como a onça parda (Puma concolor), o veadocatingueiro (Mazama gouazoubira) e o tamanduá bandeira (Myrmecophaga tridactyla). O método utilizado se mostrou eficiente no levantamento de espécies de mamíferos terrestres de médio e grande porte em área de floresta neotropical, possuindo boa aplicabilidade e vantagens em comparação a outros métodos existentes... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Floresta - Itatinga (SP); Biodiversidade; Mata Atlântica - Preservação